Consumed : the need for collective change : colonialism, climate change, and consumerism - Barber, Aja (Balance, 2021)
"In Consumed, Barber calls for change within an industry that regularly overreaches with abandon, creating real imbalances in the environment and the lives of those who do the work--often in unsafe conditions for very low pay--and the billionaires who receive the most profit. A story told in two parts, Barber exposes the endemic injustices in our consumer industries and the uncomfortable history of the textile industry, one which brokered slavery, racism, and today's wealth inequality. Once the layers are peeled back, Barber invites you to participate in unlearning, to understand the truth behind why we consume in the way that we do, to confront the uncomfortable feeling that we are never quite enough and why we fill that void with consumption rather than compassion. Barber challenges us to challenge the system and our role in it. The less you buy into the consumer culture, the more power you have. Consumed will teach you how to be a citizen and not a consumer."--Amazon website.